Dictionary of cults, sects, religions and the occult - Mather, George A.; Nichols, Larry A.; Schmidt, Alvin J. (Grand Rapids, MI Zondervan, 1993)
Includes bibliographical references.
Keywords: Religions -- dictionaries; Cults -- dictionaries; Sects -- dictionaries; Occultism -- dictionaries